HUBUNGAN ANTARA PENGETAHUAN DAN SIKAP IBU POST PARTUM DENGAN PEMBERIAN KOLOSTRUM PADA BAYI BARU LAHIR DI PUSKESMAS SAYUR MATINGGI KECAMATAN SAYUR MATINGGI - parinduri, julidia safitri (Jurnal Kesehatan Ilmiah Aufa Royhan, 2016)
Colostrum is a protective fluid that is rich in anti-infective agents and the high-protein out fromthe first to the fourth or seventh day after birth. Method is correlation. The population in this study areall mothers Post partum many as 46 people, with a accidental sampel of 46 respondents, taken tottalsampling. Data was collected through interviews using a questionnaire and then presented in afrequency distribution table and cross table.The results of this study showed p = 0.003 (p <0.05) means that there is a significant correlationbetween the respondents' knowledge by giving colostrum to the newborn, and obtained p = 1.000 (p>0.05) means that there is no significant relationship between attitude respondents with givingcolostrum to the newborn.Suggested to health workers in health centers in order to hold Vegetable Matinggi disseminationto all pregnant women in Puskesmas Vegetable Matinggi about the importance of colostrum to thenewborn.